Requirements Elicitation for Software: Modeling Techniques - Jehad Mohamed Mousa,; Amir Kamel Badr, (المجلة الدولية للحاسبات والمعلوماتية, 2022)
This research aims to introduce Goal-Oriented Requirements Engineering (GORE), defining what is meant by a goal, the main differences between goal and requirement, also the types of goals and the sources of extracting these goals, in addition, the birth of goal modelling techniques and the reason behind using goal modelling, at last, the goal-oriented approaches, early and late requirements goal modelling techniques, this research tries to get out with the result of how goal modelling is very important in requirements engineering, in order to extract the goals and requirements in correspondence to business context, which in turn will aid in better analyses and extract the functions and processes in any organization or business.